Counterfeit Currency Recognition Using Image Processing Techniques - Kailash Kumar, Nikhil Singhal, Nishant Jindal, Yogesh Bhargav (International Journal of Advanced Science and Technology, 2020)
Since the most recent couple of years, because of the extraordinary innovative advances in shading printing, copying and checking, duplicating issues have become increasingly genuine. Before, just the printing house can make a fake note, however today it is workable for any individual to print fake certified receipts essentially by utilizing a PC and a laser printer at the house. Hence the issue of proficiently checking fake banknotes from genuine ones by means of programmed machines has become increasingly significant. Fake notes are an issue of pretty much every nation except India has been hit extremely hard and has become an intense issue. There is a need to structure a framework that will support for acknowledgment of paper cash notes with quick speed and in less time. This proposed framework portrays an approach for check of Indian banknotes. The money will be looked at by utilizing picture preparing procedures. The methodology consists of various components including preparing a picture, location of edge, picture division, drawing out trademark, comparing the two pictures. The picture handling approach is talked about with MATLAB to check the parameters of note. Picture preparation includes changing the idea of a picture so as to improve its visual data for human translation. The picture handling programming is an assortment of capacities that broadens the ability of the MATLAB processing condition. The outcome will be whether the currency is real or counterfeit.